The role of behavioural competences in predicting entrepreneurial funding resource orchestration - Geoff Parkes; Mark Hart; John Rudd; Rebecca Liu (Cogent Business & Management, 2018)
This study examines how a psychometric testing tool can be used to explain, predict and measure behavioural competences and how entrepreneurs fund the firm. Reference is made to studies of personality traits. More recent studies have called for research into behaviour and competences and specifically in the finance context of orchestration of resources.The authors take a pragmatic realism perspective using a mixed method study to explore the “reality” of the entrepreneur. Cluster analysis is used to identify the relationship between behavioural competences and funding outcomes.Applying Big 5 Theory of Personality and the Great 8 Competences indicates how behaviour impacts outcomes as entrepreneurs seek to access finance. The identification of three distinct groups in this longitudinal study means belonging to one of these groups predicts likely behaviour when searching for finance.A strong behavioural characteristic which emerged, validated through interviews and psychometric testing, was an orientation towards engagement and working with other organisations. In a funding context, this manifested itself in using networks, seeking advice and sharing equity. These co-operative, collaborative characteristics are different to the classic image of the entrepreneur as a risk-taker or extrovert.The study identifies entrepreneurs who are both successful and unsuccessful in finance applications and compares behavioural competency profiles, thus overcoming the limitations of many studies that are biased towards successful enterprises.
Keywords: 650